Palonosetron and Ramosetron Compared for Effectiveness in Preventing Postoperative Nausea and Vomiting: A Systematic Review and Meta-Analysis. - EunJin Ahn; GeunJoo Choi; Hyun Kang; ChongWha Baek; YongHun Jung; YoungCheol Woo; SangSeok Lee; YeoGoo Chang (PLoS ONE)
Previous randomized controlled trials have reported conflicting findings on the superiority of palonosetron over ramosetron for preventing postoperative nausea and vomiting (PONV). Therefore, the present systematic review was registered in PROSPERO (CRD42016038120) and performed to compare the efficacy of perioperative administration of palonosetron to that of ramosetron for preventing PONV. We searched MEDLINE, EMBASE, and CENTRAL to identify all randomized controlled trials that compared the effectiveness of perioperative administration of palonosetron to that of ramosetron. The primary endpoints were defined as the incidence of postoperative nausea (PON), postoperative vomiting (POV), and PONV. A total of 695 patients were included in the final analysis. Subgroup analysis was performed through administration times which were divided into two phases: the early phase of surgery and the end of surgery. Combined analysis did not show differences between palonosetron and ramosetron in the overall incidence of PON, POV or PONV. Palonosetron was more effective than ramosetron, when the administration time for the 5-HT3 receptor antagonist was during the early phase of the operation. Otherwise, ramosetron was more effective than palonosetron, when the administration time was at the end of surgery. However, the quality of evidence for each outcome was low or very low and number of included studies was small, limiting our confidence in findings.